Dexterity and Motor Skill Development in Dentistry: A Narrative Review - R. Rajab Ali, (Asian Journal of Pharmaceutics (AJP), 2026)
The ability to work with accuracy and perfect harmony is essential for safe, effective dental care. Every clinician relies on established motor skills to manage activities effectively and minimize strain, whether they are performing everyday care or complex treatments. Over time, developments in digital simulations and motor learning theory have altered how these crucial skills are taught in dental colleges. This review aims to study the development of motor skills in dentistry, emphasizing training methodologies and assessment techniques for recording progress. It also takes into account the increasing influence of digital tools, such as virtual reality and interactive simulations, for enhancing experiential learning. The reviewed previous studies were in PubMed, Web of Science, Scopus, and Google Scholar. The selected literature searched for terms such as motor learning, psychomotor skills, dexterity evaluation, and dental education. That developing efficient motor abilities needs far more than practice. Both traditional and contemporary training methods, such as optimal theory and schema theory, provide insight into how motivation and feedback lead to improved skills. Dental students benefit from modern methods that use haptic instruments and virtual reality to practice fine movements and enhance precision. Motor skills are not only a component of dental education but are vital for competent clinical practice. Dental schools can help future professionals succeed by combining targeted instruction, practical experience, and acute use of technology.